2021
DOI: 10.1007/s00246-021-02561-w
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Transfer and Mortality in Neonates with Hypoplastic Left Heart Syndrome in California

Abstract: Maternal race/ethnicity is associated with mortality in neonates with hypoplastic left heart syndrome (HLHS). We investigated whether maternal race/ethnicity and other sociodemographic factors affect timing of transfer after birth and whether timing of transfer impacts mortality in infants with HLHS. We linked two statewide databases, the California Perinatal Quality Care Collaborative and records from the Office of Statewide Health Planning and Development, to identify cases of HLHS born between 1/1/06 and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
7
1
Order By: Relevance
“…19 Lastly, PHIS does not contain the level of granularity afforded by institutional data; anatomic and morphologic variations previously linked to poor outcomes (eg, aortic/mitral atresia, intact atrial septum), specific genetic analyses, precise details of surgical or interventional procedures, and the impacts of procedural complications on DAOH could not be evaluated. [14][15][16][17] Future studies should therefore seek to validate and expand upon the findings of the present analysis using institutional data.…”
Section: Limitationsmentioning
confidence: 81%
“…19 Lastly, PHIS does not contain the level of granularity afforded by institutional data; anatomic and morphologic variations previously linked to poor outcomes (eg, aortic/mitral atresia, intact atrial septum), specific genetic analyses, precise details of surgical or interventional procedures, and the impacts of procedural complications on DAOH could not be evaluated. [14][15][16][17] Future studies should therefore seek to validate and expand upon the findings of the present analysis using institutional data.…”
Section: Limitationsmentioning
confidence: 81%
“…Two prior studies have linked birth far from a cardiac center with mortality in infants with critical congenital heart disease (Kaltman et al, 2020; Morris et al, 2014). However, many smaller studies, including one by our own team, have not found transfer after birth to be associated with a higher risk of mortality (Bennett et al, 2010; Fixler et al, 2012; Purkey et al, 2021). Future studies should investigate if other outcomes, including long‐term morbidities, are associated with birth location and transfer.…”
Section: Discussionmentioning
confidence: 94%
“…Our group recently published data on transfer patterns in neonates with HLHS in California from 2006 to 2011. We found that late transfer was more likely in low birthweight infants and infants born to U.S.‐born Hispanic and Black mothers (Purkey et al, 2021). However, this analysis did not address whether or not infants were born close to home or the distance between the birth and repair hospitals.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some children in whom the management intent was not primarily comfort care still do not survive after the diagnosis is made. They are often high risk (low birthweight, low five-min Apgar score, or have other major congenital anomalies), 7 too ill to make it to the operating room or to a facility with treatment capabilities, inadequately resuscitated prior to transfer, or decompensate during transport or on arrival at the treatment facility prior to intervention. Pretransport and/or presurgical mortality occurs in low-resource settings where patients must travel long distances to reach care.…”
Section: Death After Receiving a Diagnosismentioning
confidence: 99%